What is thyroid function in your just-diagnosed cancer patient? - Hercbergs, Aleck; Mousa, Shaker A.; Lin, Hung-Yun; Davis, Paul J. (Frontiers in Endocrinology, 2023)
The principal hormonal product of the thyroid gland, L-thyroxine (T4), is a prohormone for 3,3’,5-triiodo-L-thyronine, T3, the major ligand of nuclear thyroid hormone receptors (TRs). At a cell surface thyroid hormone analogue receptor on cancer cell and endothelial cell plasma membrane integrin αvβ3, however, T4 at physiological concentrations is biologically active and is the major ligand. At this site in solid tumor cells, T4 nongenomically initiates cell proliferation, is anti-apoptotic by multiple mechanisms, supports radioresistance and enhances cancer-related angiogenesis. In contrast, hypothyroidism has been reported clinically to slow tumor growth. At physiological levels, T3 is not biologically active at the integrin and maintenance of euthyroidism with T3 in cancer patients may be associated with slowed tumor proliferation. Against this background, we raise the possibility that host serum T4 levels that are spontaneously in the upper tertile or quartile of the normal range in cancer patients may be a factor that contributes to aggressive tumor behavior. Recent observations on tumor metastasis and tumor-associated propensity for thrombosis due to T4 also justify clinical statistical analysis for a relationship to upper tertile hormone levels. That reverse T3 (rT3) may stimulate tumor growth has recently been reported and thus the utility of adding this measurement to thyroid function testing in cancer patients requires assessment. In summary, T4 at physiological concentrations promotes tumor cell division and aggressiveness and euthyroid hypothyroxinemia arrests clinically advanced solid tumors. These findings support the clinical possibility that T4 levels in the upper tertile of the normal range require examination as a tumor supporting factor.